Virtual Exploration of Mount Bromo Caldera Stratigraphy Through Virtual Reality Environment Media in Geography Learning - Linda Sustika; Cahya Darmawan; Andrias (CV Bumi Spasial, 2026)
This research focuses on the development of a Virtual Reality Environment (VRE) designed for geography instruction, specifically targeting volcanic stratigraphy within the Mount Bromo region. Subsequently, the study evaluates user experience (UX) to determine the media's technical usability and its capacity for pedagogical engagement. This virtual reality environment media is produced through a series of scientific research and development procedures (plomp model) which comprises three distinct phases: preliminary research, prototyping, and assessment. User response data were gathered via the User Experience Questionnaire (UEQ) administered to 25 tenth-grade students, evaluating both pragmatic and hedonistic qualities. The user experience evaluation indicated that the VRE media effectively facilitates the identification of volcanic rock layers. The results demonstrated high levels of clarity and efficiency, suggesting that the immersive environment assists students in distinguishing complex stratigraphic features that are otherwise difficult to observe in traditional settings. In addition, they indirectly stated that this VRE media is efficient enough to explore learning to distant places, useful, exciting, interesting, motivate them to learn, and has a good novelty for exploring geography learning.